2011 Proceedings IEEE INFOCOM 2011
DOI: 10.1109/infcom.2011.5935075
|View full text |Cite
|
Sign up to set email alerts
|

Joint distributed access point selection and power allocation in cognitive radio networks

Abstract: Spectrum management has been identified as a crucial step towards enabling the technology of the cognitive radio network (CRN). Most of the current works dealing with spectrum management in the CRN focus on a single task of the problem, e.g., spectrum sensing, spectrum decision, spectrum sharing or spectrum mobility. In this work, we argue that for certain network configurations, jointly performing several tasks of the spectrum management improves the spectrum efficiency. Specifically, we study the uplink reso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…The threshold-strategy definition (5) states that a player transmits on channel k if the channel power gain h k i is the largest among all the channels and h k i is greater than a threshold h ith . As a consequence of the special form of threshold strategies, we can denote the strategy profile of the players by simply specifying their threshold vector s th := (h ith , i ∈ N ).…”
Section: A Threshold Strategiesmentioning
confidence: 99%
“…The threshold-strategy definition (5) states that a player transmits on channel k if the channel power gain h k i is the largest among all the channels and h k i is greater than a threshold h ith . As a consequence of the special form of threshold strategies, we can denote the strategy profile of the players by simply specifying their threshold vector s th := (h ith , i ∈ N ).…”
Section: A Threshold Strategiesmentioning
confidence: 99%
“…Thus,wm can be interpreted as the downlink transmit beamformer of the virtual BS to user m, which contains the power information. Similarly, θm is the noise power at user m. Moreover, the downlink transmit power is constrained by (6), and the noise power by (5).…”
Section: Problem Formulation and Algorithmmentioning
confidence: 99%
“…The popular strategy is to formulate the problem from the perspective of sparse beamforming, i.e., introducing some sparse constraints to the linear beamformers while optimizing the network performance in, e.g., spectrum efficiency [4][5][6], user fairness [7], and power efficiency [5,8,9], etc. However, most current works focus on the downlink transmission.…”
Section: Introductionmentioning
confidence: 99%
“…The decision is generally made by the client locally and selfishly, which has been analyzed through game theory in different network settings, e.g., wireless access networks [24] [7] [19], cognitive radio networks [11], and cellular networks with linear topologies (linear cellular networks) [15]. It has been shown that the selfish behavior does not necessarily converge to the optimal equilibrium [23].…”
Section: Related Workmentioning
confidence: 99%
“…Optimized decentralized association algorithms [14] [23] [11] try to achieve global optimum with local client measurements. Yet certain simplifications have been made in these pioneering studies, e.g., uniform throughput among all users or linear topology, which can hardly be extended to general network settings.…”
Section: Related Workmentioning
confidence: 99%